2020
DOI: 10.7759/cureus.10009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gallstone Formation in Aberrant Extrahepatic Biliary Tract Anatomy: A Review of Literature

Abstract: The age-long mnemonic of '5Fs' (fat, female, fertile, forty, and fair) has traditionally been used in medical school instructions to describe the risk factors for gallstone disease. However, evidence suggests that aberrant extrahepatic biliary tract (EHBT) anatomy may contribute significantly to the risk of gallstone disease. This review explores the anatomy and embryological bases of EHBT variations as well as the prevalence of these variations. Also, we discuss the risk factors for gallstone formation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Variations in the anatomy of the cystic duct are common findings in imaging studies and cholecystectomy reports, occurring in 18%-23% of individuals [2].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the anatomy of the cystic duct are common findings in imaging studies and cholecystectomy reports, occurring in 18%-23% of individuals [2].…”
Section: Discussionmentioning
confidence: 99%
“…Gallstones in the bile duct are the major indication endoscopic retrograde cholangiopancreatography (ERCP) and have significant impact on quality of life and productivity of the patients. 14,15 There has been significant improvements in management strategies in recent decades with rapid advancement and evolution of research in biliary system. 14 Our study included 139 patients meeting inclusion criteria, of these 139 study cases, 49 (35.3%) were male and 90 (64.7%) were female patients with bile duct stone.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 There has been significant improvements in management strategies in recent decades with rapid advancement and evolution of research in biliary system. 14 Our study included 139 patients meeting inclusion criteria, of these 139 study cases, 49 (35.3%) were male and 90 (64.7%) were female patients with bile duct stone. Odemis et al 16 has also reported 62% female patients with bile duct gall stones, similar to our results.…”
Section: Discussionmentioning
confidence: 99%